AKUNTABILITAS DAN TRANSPARANSI PADA LAPORAN KEUANGAN PARTAI (Studi Kasus pada Kantor DPD Partai Demokrat Provinsi Jawa Timur) - Wiwid Widayanti; Maswar Patuh Priyadi; Lilis Ardini (Akademi Akuntansi YKPN Yogyakarta, 2019)
This study aims to determine and interpret accountability and transparency in the East Java Provincial Democratic Party DPD financial report consisting of internal financial reports, campaign finance reports and political assistance reports and the implementation of the AD and ART of the East Java Provincial Democratic Party. The object used in this research is the DPD office of the Democratic Party of East Java Province with interpretive qualitative research methods with ethnometodology as an approach, there are four informants in the research using interview, observation and documentation research methods and using data analysis techniques starting from data reduction, display data and verify or draw conclusions. The results showed that internal financial reports had fulfilled accountability to internal political parties but were not yet transparent to the public, campaign finance reports had met accountability and transparency, political assistance reports had met accountability but were not yet transparent to the public, and the implementation of AD and ART DPD Provincial Democratic Party East Java has been implemented well.